The compromised republic : an inquiry into the development of underdevelopment - Siddiky, Chowdhury Irad Ahmed (Dhaka : Oriental KAS Publishers, 2003)
Research study on development economics and regional economic disparities in Bangladesh.
Includes bibliographical references.
Keywords: Development economics -- Bangladesh; Bangladesh -- Economic conditions -- Regional disparities